Feeling anxious? The mechanisms of vocal deception in tufted capuchin monkeys. (August 2017) - Kean, Donna; Tiddi, Barbara; Fahy, Martin; Heistermann, Michael; Schino, Gabriele; Wheeler, Brandon C.
Abstract : An ability to deceive conspecifics is thought to have favoured the evolution of large brains in social animals, but evidence that such behaviours require cognitive complexity is lacking. Tufted capuchin monkeys ( Sapajus spp.) have been documented to use false alarm calls during feeding in a manner that functions to deceive competitors. However, comparative evidence suggests that the production of vocalizations by nonhuman primates is largely underpinned by emotional mechanisms, calling into question more cognitive interpretations of this behaviour. To determine whether emotional states are plausibly necessary and sufficient to proximately explain deceptive alarm call production, we examined the association between self-directed behaviours (SDBs), as a proxy for anxiety, and the production of spontaneous false alarm calls among tufted capuchins. Specifically, we predicted that if anxiety is necessary for the production of false alarms, then individuals that produce spontaneous false alarms should exhibit more SDBs in those contexts in which they call. If anxiety is also sufficient to explain the false alarm call production, then we predicted that individuals that call more in a given context would show higher rates of SDBs in that context, and that high rates of calling would be temporally associated with high rates of SDBs. Our results support the contention that states of anxiety are necessary for an individual to spontaneously produce false alarms, but that such states are not sufficient to explain patterns of calling. The link between anxiety and deceptive calling thus appears complex, and cognitively based decision-making processes may play some role in call production. Highlights: We test if deceptive alarm calls are associated with anxiety in capuchin monkeys. Monkeys that give deceptive calls self-scratch more in contexts in which they call. Production of deceptive calls thus appears to be associated with anxiety. Being in a state of anxiety may be a necessary precondition for deceptive calling. Such states are, however, insufficient to explain whether or not a call is given.